Performing optimal power flow studies for the microgrid - Yap, Malvern Zong Han (Nanyang Technological University, 2021)
Optimal Power Flow (OPF) is a collection of power optimisation models aimed at determining the best-possible level of operation of electrical power generating units with the purpose of dispatching power in an economic manner. Due to the complexity of an electrical transmission and distribution network, the deliverance of power is represented through non-linear non-convex mathematical functions which reflects the network’s physical characteristics, posing a challenge in real life as such must be resolved in short intervals while ensuring that the ever-changing consumers’ demand is met.